MOTIVASI SEBAGAI PENGUBAHAN PERILAKU - Lis Yulianti Syafrida Siregar (IAIN Padangsidimpuan, 2020)
Motivation is encouragement that came from humans with awareness or unawareness for doing something that concerns with a certain purpose. As we know the behavior of humans is influenced by motivation or encouragement for the importance that accomplishes requirement from an individual. Alteration of behavior is the psychology that relates to the analysis and changing of human behaviorÂ